FAKTOR YANG MEMPENGARUHI PERILAKU BERALIH KONSUMEN DALAM MENGGUNAKAN KARTU SELULER - Joko Santoso, Moh. (Manajemen Bisnis, 2013)
Moh. Joko SantosoPT. Astra Agro Lestari, TbkE-mail: m.joko.santoso@yahoo.co.idABSTRACTThis research aims to determine the factors affecting consumer switching behaviour on cellular card inMalang City. Consumer switching behaviour factors included customer service, knowledgeable employees,waiting time to get the customer service, error billing, network coverage, frequent network problem, newscheme, plan for different age,value added service, call rates, hidden charges, short message service charges,internet charges, recharge facilities, offered by competitor family and friend, fancy number, and rechargecost. Consumer switching behaviour in cellular card seen during the last six months. Respondents were cardusers who have used cellular card at least 6 months. The sum of respondent are 100 users who are selectedby purposive sampling. Data were collected by using questionnaires. The data analysed by using logisticregression enter method and backward stepwise. Based on the results of logistic regression analysis exemplifiedthat the constant significance value was less than 0.05. This meant that the factors of consumerswitching behaviour had a significant effect in cellular card. The factors affect consumer switching behaviourhad influenced at 37.6%, and 62.4% influenced by other factors outside this study. Finnaly, the fancy numberwas the most dominant factors which could influence consumer switching behaviour.Keywords: cellular card user, consumer behavior, switching behavior